Association of monetary diet cost of foods and diet quality in Spanish older adults - Bouzas, Cristina; Pastor, Rosario; García, Silvia; Monserrat-Mesquida, Margalida; Martínez-González, Miguel Ángel; Salas-Salvadó, Jordi; Corella, Dolores; Schröder, Helmut; Martínez, J. Alfredo; Alonso-Gómez, Ángel M.; Wärnberg, Julia; Vioque, Jesús; et al. (Frontiers in Public Health, 2023)
Background: A major barrier for a healthy diet may be the higher price of healthy foods compared to low-quality foods.To assess the association of monetary cost of food and diet quality in Spanish older adults at high risk of cardiovascular disease.Methods: Cross-sectional analysis carried out in Spanish older adults (n=6838; 48.6% female).A validated food frequency questionnaire was used to assess dietary intake. Metabolic syndrome severity, adherence to the Mediterranean diet (MedDiet), adherence to a provegetarian dietary pattern, and dietary inflammatory index were assessed. Economic cost of foods was obtained from the Spanish Ministry of Agriculture Fisheries and Food database (2015-2017, period of time when the participants were recruited). Total cost of diet adjusted per 1000 kcal was computed.Results: Healthier dietary pattern was associated with higher cost of the diet. Higher adherences to the MedDiet, anti-inflammatory diet, and the healthful version of the provegetarian dietary pattern were related to higher cost of the diet.Higher diet quality was associated with a higher dietary cost of the diet per 1000 kcal/day. Food prices can be an important component of interventions and policies aimed at improving people's diets and preventing diet-related chronic diseases.